Numerical simulation and analysis of the pulsed neutron source method measuring the prompt neutron decay constant of a Godiva-like subcritical facility. (March 2021) - Gao, Yi; She, Ruogu; Li, Jinghong; Fu, Xuedong; Zhong, Bin; Yang, Bo
Abstract: The theory and method of the pulsed neutron source (PNS) method measuring the prompt neutron decay constant α 0 of a subcritical system was introduced. Using the Monte Carlo code JMCT, the neutron transport process in a Godiva-like subcritical facility was simulated. The α 0 value of the facility was obtained with PNS method, and was compared with the α - k power iteration result. To investigate the factors affecting the calculated α 0 value of the PNS method, the system response, the fitting residual distributions, and the neutron energy spectra of different time intervals were analyzed. It is observed that the statistical fluctuation is the key factor leading to the inaccuracy of the α 0 calculation value of the facility. Furthermore, to obtain an effective α 0 value with the PNS method, the reasonable width of fitting time window was discussed by analyzing the relationship of the calculated α 0 values and the fitting time width in this paper. Graphical abstract: Image 1 Highlights: The factors affecting the accuracy of α 0 are investigated by Monte Carlo analyses. The statistical fluctuation is the key factor leading to the inaccuracy of α 0 . To obtain an effective α 0 value, the fitting time width must be chosen reasonably.